2013
DOI: 10.2131/jts.38.875
|View full text |Cite
|
Sign up to set email alerts
|

<i>Garcinia vilersiana</i> bark extract activates the Nrf2/HO-1 signaling pathway in RAW264.7 cells

Abstract: Garcinia vilersiana is a traditional medicinal plant in Vietnam. The petroleum ether extract of stem bark of Garcinia vilersiana (GVE) was prepared to evaluate its potential to activate Nrf2, a transcription factor of antioxidant and detoxifying enzymes. Exposure of mouse macrophage RAW264.7 cells to GVE (0.625-2.5 µg/ml) resulted in a significant activation of Nrf2, as evaluated by nuclear accumulation of this transcription factor, and increased antioxidant response element (ARE) binding activity in a time- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This meant that KC inhibited NO production partly by upregulating the expression of HO-1 in RAW264.7 cells. The Nrf2 is a transcription factor that regulates expression of HO-1 [39]. Further findings demonstrated that Nrf2 was decreased in the cytosols of KC-treated LPS-stimulated RAW 264.7cells, but their DNA-binding activities were concomitantly increased, implying that KC's mediated increase in HO-1 expression was as a result of its action on Nrf2.…”
Section: Discussionmentioning
confidence: 92%
“…This meant that KC inhibited NO production partly by upregulating the expression of HO-1 in RAW264.7 cells. The Nrf2 is a transcription factor that regulates expression of HO-1 [39]. Further findings demonstrated that Nrf2 was decreased in the cytosols of KC-treated LPS-stimulated RAW 264.7cells, but their DNA-binding activities were concomitantly increased, implying that KC's mediated increase in HO-1 expression was as a result of its action on Nrf2.…”
Section: Discussionmentioning
confidence: 92%
“…The nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that regulates expression of antioxidant and detoxifying genes including heme oxygenase-1 (HO-1). 34) HO-1 plays an important role in the regulation of oxidative stress and inflammatory responses. It is well known that HO-1 is a highly inducible and rate-limiting protein that catalyzes the degradation of heme to carbon monoxide (CO), ferrous iron and biliverdin.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we and others have found little evidence for de novo androgen synthesis in clinical CRPC samples. Moreover, we have previously shown that androgen precursors induced cell growth and AR target gene expression in vitro, but with undetectable CYP17A1‐dependent conversion into testosterone, indicating either direct AR binding or conversion rather than de novo synthesis as a driver of cell growth …”
Section: Introductionmentioning
confidence: 99%